A General Synthesis of Tris-Indole Derivatives as Potential Iron Chelators - C. Whitlock; R. Carpenter; R. Sears (Molecules, 2005)
The development of a novel route for the synthesis of a new class of compounds is described. The first tripodal, tris-indole amines are prepared by straightforward routes.